Pojęcie pola metaforycznego w poetyce kognitywnej - Ślósarska, Joanna (Przestrzenie Teorii, 2007)
The paper presents basic conceptualisations of the metaphoric field in the views of N. Babuts, G. Lakoff, M. Johnson, M. Turner, R. W. Gibbs, and R. Tsur. In the course of considering these views the following problems are discussed: differentiation of the conceptual from linguistic metaphors, hypothesis of a cognitive base for linguistic creation of poetical tropes, creation of poetical figures in relation to standard metaphors in natural language, dynamics of the processes of conceptual and linguistic métaphorisations, categories of the mental image and of the vantage point. The whole discussion is placed within a context of the two basic paradigms of cognitive science - mental and empirical.